A novel thermoelectric-electrochemical cell based on redox couple and its preparation
By introducing microelectrodes into the electrolyte of thermoelectric-electrochemical batteries, the cyclic reaction is promoted, and the problems of low Seebeck coefficient and complex and expensive processes of existing thermoelectric-electrochemical batteries are solved, and the effect of high Seebeck coefficient and continuous and stable energy supply is achieved.
Patent Information
- Application Number
- CN202210863330.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-20
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-07-20
AI Technical Summary
The Seebeck coefficient of existing thermoelectric-electrochemical batteries is low, making it difficult to achieve sustainable and stable ambient temperature power supply, and the process is complex and expensive.
By introducing microelectrodes, such as oxide particles and semiconductor compound particles, the cell cycle reaction is promoted and the Seebeck coefficient is improved.
The Seebeck coefficient and output power of thermoelectric-electrochemical batteries are significantly improved, and the continuous and stable energy supply under temperature differences is achieved, reducing the cost and complexity of the battery.
Smart Images

Figure CN115207427B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of thermoelectric-electrochemical cells, and more specifically, relates to a novel thermoelectric-electrochemical cell based on a redox couple and its preparation. The novel thermoelectric-electrochemical cell is a thermoelectric-electrochemical cell based on a composite of a redox couple and microelectrodes. Background Art
[0002] With the rapid development of the Internet of Things, more and more distributed sensors are being used, and the power supply methods of various sensors have been widely studied: using cables for power supply is costly and inconvenient to maintain; using dry batteries and rechargeable batteries requires regular replacement, and when the number of sensors reaches a certain level, the maintenance workload is also very large; using environmental energy for power supply is the most ideal method, and solar cells, thermoelectric power generation devices, etc. have been increasingly studied.
[0003] Most micro sensors only require milliwatt or even microwatt-level power, but require an operating voltage of around 2V or above. Traditional bulk thermoelectric materials can only generate a voltage of tens to hundreds of microvolts per degree Celsius temperature difference, so more than hundreds of pairs of PN junctions are required to be connected in series to achieve the voltage required for the device to work. Therefore, ionic thermoelectric materials with huge Seebeck coefficients have received more and more attention. However, since temperature-driven ionic conduction is difficult to form a sustainable electrical transport circuit, the energy supply cannot be sustained and can only be achieved in a pulsed manner. Therefore, in the field of thermoelectric materials, materials with high Seebeck coefficients and materials that can stably and continuously utilize ambient temperature for energy supply have yet to be developed, and have broad prospects in the application of IoT sensor energy supply.
[0004] Redox couples can undergo reversible redox reactions, and the rates of their reversible reactions in different directions can be regulated by temperature. A temperature difference is established at both ends to obtain an electromotive force. Moreover, the Seebeck coefficient equivalent to this electromotive force is much larger than that of traditional bulk thermoelectric materials, and compared to ionic thermoelectric materials, it can continuously supply energy when a temperature difference is established. Therefore, thermoelectric-electrochemical cells based on redox couples have great potential in absorbing environmental energy to supply micro-nano power to devices.
[0005] However, the Seebeck coefficient of basic thermoelectric-electrochemical cells needs to be further improved to enhance their competitiveness in commercial applications. In addition, the existing technology for improving the performance of thermoelectric-electrochemical cells is mainly achieved through complex electrode structure design and surface modification, but there are still defects such as complex and expensive processes. Summary of the invention
[0006] In view of the above defects of the prior art and the demand for continuous energy supply, the purpose of the present invention is to provide a new type of thermoelectric-electrochemical cell based on redox couple and its preparation, by introducing microelectrodes (oxide particles, semiconductor compound particles), utilizing the combination of redox couple and microelectrode, the battery cycle reaction of the thermoelectric-electrochemical cell is promoted, the reaction cycle is strengthened, and a thermoelectric-electrochemical cell with a high Seebeck coefficient is obtained, which can be suitable for the conversion of low-grade thermal energy into electrical energy under various working conditions, can solve the limitations of ordinary redox couples and low Seebeck coefficients of inorganic bulk thermoelectric materials in practical applications, and the problems of complex and expensive thermoelectric-electrochemical cell processes, and can realize a thermoelectric-electrochemical cell with high output voltage and continuous and stable energy supply.
[0007] To achieve the above objectives, according to one aspect of the present invention, a new thermoelectric-electrochemical cell based on a redox couple is provided, characterized in that a redox couple and microelectrodes are dispersed in the electrolyte of the cell, and the microelectrodes are selected from oxide micro-nano particles and semiconductor compound micro-nano particles.
[0008] As a further preferred embodiment of the present invention, the redox couple is specifically Fe(CN)6 3- / Fe(CN)6 4- Redox couple, I - / I3 - Redox couple, Fe 2+ / Fe 3+ One of the redox couples.
[0009] As a further preferred embodiment of the present invention, the oxide material of the oxide micro-nano particles is specifically at least one of TiO2, ZnO, ZrO2, In2O3, ATO, FTO, ITO, AZO, and SnO2;
[0010] The semiconductor compound of the semiconductor compound micro-nano particles is specifically at least one of a Bi2Te3-based compound, a SnTe-based compound, a MgAgSb-based compound, and an InSb-based compound; preferably, the Bi2Te3-based compound is Bi 0.4 Sb 1.6 Te3、Bi2Te 2.7 Se 0.3 At least one of .
[0011] As a further preferred embodiment of the present invention, the micro-electrode is the oxide micro-nano particles, and the oxide micro-nano particles are specifically nano oxide particles, and the concentration of the oxide micro-nano particles in the electrolyte is 0.3-1.5 g / mL.
[0012] As a further preferred embodiment of the present invention, the micro-electrode is the semiconductor compound micro-nano particles, and the semiconductor compound micro-nano particles are specifically micron-sized semiconductor compound particles, and the concentration of the semiconductor compound particles in the electrolyte is 1.2-3.2 g / mL.
[0013] As a further preferred embodiment of the present invention, the semiconductor compound micro-nanoparticles are specifically semiconductor compound microparticles, which are preferably obtained by grinding or planetary ball milling a smelted semiconductor compound block; more preferably, the rotation speed used in the planetary ball milling treatment is 200-500rpm, and the processing time is 2-5h.
[0014] According to another aspect of the present invention, the present invention provides a method for preparing the novel thermoelectric-electrochemical cell based on the redox couple, characterized in that it comprises the following steps:
[0015] (S1) dissolving a redox couple in deionized water to prepare an initial electrolyte solution;
[0016] (S2) mixing the microelectrode with the initial electrolyte solution obtained in step (S1) and dispersing them evenly to obtain a composite electrolyte slurry;
[0017] (S3) Using the composite electrolyte slurry obtained in the step (S2) as a battery electrolyte, a new thermoelectric-electrochemical battery based on a redox couple is constructed.
[0018] As a further preferred embodiment of the present invention, in the step (S3), the battery electrolyte is adsorbed on the sponge, and the two are packaged together inside the battery; the sponge is preferably a melamine sponge or a polyurethane sponge.
[0019] As a further preferred embodiment of the present invention, in the step (S2), the dispersion is specifically carried out by dispersing the microelectrodes in the electrolyte solution by means of magnetic stirring, ball milling or ultrasonic treatment;
[0020] Preferably, the magnetic stirring is carried out at a speed of 300-600 rpm for at least 20 min;
[0021] Ball milling is performed in an agate ball milling jar using agate ball milling beads at a speed of 150-250 rpm for 10-30 min;
[0022] Ultrasonication is to seal the mixed slurry in a serum bottle and ultrasonicate it for more than 1 hour, and shake it every 15-30 minutes during the treatment process.
[0023] As a further preferred embodiment of the present invention, the two electrodes of the battery of the present invention can be placed at the hot end and the cold end respectively, and the distance between them can be adjusted according to the position distance of the hot end and the cold end. For example, it can be suitable for a scenario where the distance between the hot end and the cold end is 3-15 mm.
[0024] Through the above technical scheme conceived by the present invention, compared with the prior art, the present invention introduces micro-electrodes, such as bismuth telluride, indium oxide, zirconium oxide, etc., into the electrolyte based on the redox couple, so that many small cycles can be embedded in the overall cycle reaction of the battery. In the prior art, the cyclic battery reaction only occurs on the surface of the electrodes at both ends, and the redox couple cycle efficiency is low; while the present invention greatly enhances the cycle of the battery reaction by introducing micro-electrodes as relay stations for the cycle reaction, so that the battery has a higher Seebeck coefficient.
[0025] The present invention greatly improves the Seebeck coefficient of the thermoelectric-electrochemical cell by introducing microelectrodes as cyclic reaction sites into the redox couple electrolyte solution; and the numerous microelectrodes as cyclic reaction sites can greatly reduce the distance that the electrolyte ions have to migrate during the cycle, thereby greatly reducing the internal impedance of the battery. Therefore, a higher output voltage and power can be obtained under the same temperature difference. Taking Example 1 below as an example, 1mL 0.4MFe(CN)6 3- / Fe(CN)6 4- Add 2.4g of micron-grade Bi into the electrode solution. 0.4 Sb 1.6 Te3 particles are used to prepare electrolyte slurry, which is filled in a silicone tube with an inner diameter of 5 mm. Silicone rubber or epoxy resin is used to encapsulate gold-plated copper column electrodes or graphite electrodes at both ends of the silicone tube to obtain a thermoelectric-electrochemical cell with a high Seebeck coefficient, which increases the Seebeck coefficient of the pure redox couple electrolyte solution from 1.4 mV / K to 4.11 mV / K, and the output power is 0.1 W / m 2 Increased to 0.9W / m 2 More importantly, taking Example 5 as an example, the prepared thermoelectric-electrochemical battery has the same electrical properties as other traditional dry batteries, and can increase the open circuit voltage and output power by connecting in series and parallel. It can be seen that the new high-energy thermoelectric-electrochemical battery in the present invention can continuously and stably supply electrical appliances under temperature difference conditions, and can be particularly applied to unattended Internet of Things sensors, etc.
[0026] The traditional way to improve the electrical performance of thermoelectric-electrochemical cells based on redox pairs is mainly through the modification of battery electrodes and the complex design of the surface, which has the defects of complex process, high cost and single electrode shape. In the present invention, by introducing cheap micro-electrodes (preferably with the support of sponges with different pores), a technical path for improving the Seebeck coefficient of batteries with simple preparation process, low cost and new principle is provided. Based on the present invention, electrode interface reactions can be introduced inside the thermal battery, thereby shortening the cyclic migration distance of the redox pairs; and based on the present invention, micro-nano particles of specific materials can also be introduced as micro-electrodes (such as oxides such as TiO2, ZnO, ZrO2, In2O3, ATO, FTO, ITO, AZO, SnO2, and semiconductor materials such as Bi2Te3, SnTe, MgAgSb, and InSb), which can further reduce the solution / electrode interface contact resistance and reduce the redox reaction barrier, so that the Seebeck coefficient and output power density of the thermoelectrochemical battery can be optimized simultaneously. Furthermore, considering the sedimentation problem of micro-nano particles in the electrolyte solution during long-term application, if the thermoelectrochemical cell is prepared into a gel state by referring to the thermoelectric gel method, although the problem of electrode sedimentation can be solved, the migration of the redox couple in the battery will be seriously deteriorated, which is not worth the loss; in view of this, the present invention can especially use the electrolyte in conjunction with the sponge, and the sponge can absorb the battery electrolyte. Although the microelectrodes still partially settle, there are still many microelectrodes suspended in the electrolyte solution, realizing the long-term effective application of the thermoelectrochemical cell. In addition, due to the fluidity of the electrolyte slurry (the sponge shape is also flexible), the new thermoelectric-electrochemical cell obtained based on the present invention can be prepared into a flexible multi-morphological battery, which is suitable for complex heat source surfaces, greatly improving the application range of the battery.
[0027] In summary, the novel thermoelectric-electrochemical battery in the present invention has excellent thermoelectric performance by using a cheap and simple preparation process to increase the Seebeck coefficient and power density of the battery by several times; in addition, due to the fluidity of the electrolyte slurry (the supporting sponge used is preferably also flexible), the battery in the present invention is suitable for various complex heat source surfaces, which greatly expands the application scenarios of the battery. It is a novel thermoelectric-electrochemical battery with great application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Bi in Example 1 of the present invention 0.4 Sb 1.6 Particle size distribution of Te3 microelectrode. Similar to the conventional particle size test, D V (10) indicates that the particle size of the first 10% of particles is less than 0.767 μm; D V (50) indicates that the particle size of the first 50% of particles is less than 2.79 μm; DV (90) indicates that the first 90% of the particles have a size less than 12.4 μm.
[0029] Figure 2 Compared with the battery with pure redox couple electrolyte solution (only 0.4M Fe(CN)6 in the electrolyte), the new thermoelectric-electrochemical battery in Example 1 of the present invention 3- / Fe(CN)6 4- , without introducing Bi 0.4 Sb 1.6 Te3) impedance diagram; it can be seen that the impedance is significantly reduced.
[0030] Figure 3 The curves showing the change of the open circuit voltage of the novel thermoelectric-electrochemical battery with the temperature difference in Examples 1-4 of the present invention.
[0031] Figure 4 It is a picture of the new thermoelectric-electrochemical series battery pack in Example 5 of the present invention, a curve of the change of open circuit voltage with temperature difference and a display of driving electrical appliances; wherein, Figure 4 a in the figure corresponds to the picture of the new thermoelectric-electrochemical tandem battery pack, and the side length of the device shown in the figure is 105 mm; Figure 4 b in the figure corresponds to the curve of open circuit voltage changing with temperature difference; Figure 4 The c in the figure corresponds to a physical display photo of an electrical appliance driven by series-connected batteries.
[0032] Figure 5 This is a curve showing how the open circuit voltage of the novel thermoelectric-electrochemical battery in Examples 6-7 of the present invention changes with temperature difference.
[0033] Figure 6 This is a schematic diagram of the working principle of the new thermoelectric-electrochemical battery with high Seebeck coefficient and low impedance in the present invention; wherein, Figure 6 a in the figure corresponds to a device using a pure redox couple electrolyte solution. Figure 6 b in the figure corresponds to a device using a redox couple solution + microparticles (these microparticles are used as microelectrodes). When the electrolyte solution is equivalent, the device using the electrolyte solution + microparticles can provide a larger voltage and current to the outside. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0035] Based on the present invention, taking the preparation of a semi-solid flexible thermoelectric-electrochemical battery as an example, the preparation of the slurry may include the following steps:
[0036] (1) dissolving a redox couple in deionized water to prepare an initial electrolyte solution;
[0037] (2) preparing microelectrodes and mixing them with the electrolyte solution in step (1), dispersing the microelectrodes in the electrolyte solution by magnetic stirring, ball milling, ultrasound, etc., thereby obtaining a composite electrolyte slurry;
[0038] (3) cutting the sponge into a shape suitable for the battery packaging shell and the battery electrodes, and filling the sponge into the battery packaging shell;
[0039] (4) slowly injecting the composite electrolyte slurry in step (2) into the mixture of the sponge and the battery shell in step (3), so that the electrolyte slurry penetrates into the gaps in the sponge and fills it completely, and after packaging the electrodes, a thermoelectric-electrochemical battery with a high Seebeck coefficient can be obtained.
[0040] Among them, in step (2), the amount of microelectrode added can be adjusted according to its size and specific gravity; for example, the amount of nano oxide particles added can be 0.3-1.5g / mL; the amount of micron-sized semiconductor compound particles added can be 1.2-3.2g / mL. Taking the oxide particles as nanometer level as an example, commercial nano oxide particles can be purchased; and in order to obtain semiconductor compound micro-nano particles, the molten block can be processed by grinding or planetary ball milling to obtain micron-sized semiconductor compounds (the specific parameters of grinding or planetary ball milling can be flexibly adjusted according to actual conditions; taking planetary ball milling as an example, the rotation speed and processing time of the planetary ball milling can be adjusted according to the physical properties of the material, for example, the ball milling can be carried out at a rotation speed of 200-500rpm for 2-5h). In addition, the semiconductor can be, for example, a Bi2Te3-based semiconductor, a SnTe-based semiconductor, a MgAgSb-based semiconductor, an InSb-based semiconductor, and element doping is allowed. For example, the Bi2Te3-based semiconductor can be a doped Bi2Te3-based semiconductor, such as Bi 0.4 Sb 1.6 Te3、Bi2Te 2.7 Se 0.3 .
[0041] The sponge is insulating and hydrophilic. Depending on the compounding amount and size of the microelectrode, melamine sponge, polyurethane sponge, etc. with suitable pores can be directly purchased.
[0042] The battery packaging shell can be made into different forms according to different heat sources, and the electrodes can be processed into different shapes according to flat and arc-shaped heat sources without additional processing; the battery can also be prepared into a flexible soft-pack battery to be suitable for a variety of complex heat source surfaces.
[0043] The packaging method can be one of silicone rubber, epoxy resin, wire ties, bolts, etc.
[0044] Fe(CN)6 with negative temperature coefficient 3- / Fe(CN)6 4- and positive temperature coefficient resistor I - / I3 - , Fe 2+ / Fe 3+ Taking the redox couple as an example, the novel thermoelectric-electrochemical cell of the present invention requires the following raw materials in its preparation process:
[0045] Potassium ferrocyanide / potassium ferrocyanide trihydrate as an electrode for Fe(CN)6 3- / Fe(CN)6 4- Donor, potassium iodide / iodine as the electron pair I- / I3-donor, iron trifluoromethanesulfonate / ferrous trifluoromethanesulfonate as Fe 2+ / Fe 3+ Donors include nano zirconium oxide, nano indium oxide, nano zinc oxide, micron Bi 0.4 Sb 1.6 Te3, micron Bi2Te 2.7 Se 0.3 etc. as microelectrodes, battery casings with pre-designed shapes, and battery electrodes.
[0046] In practical application, the positive electrode and negative electrode of the novel thermoelectric-electrochemical cell based on the redox couple of the present invention can be placed at the hot end and the cold end (such as Figure 6 As shown in b in the figure, the distance between the battery electrodes can be adjusted according to the position distance between the hot end and the cold end. For example, it can be applied to scenarios where the distance between the hot end and the cold end is 3-15 mm.
[0047] The following are specific embodiments:
[0048] Example 1
[0049] Potassium ferrocyanide / potassium ferrocyanide trihydrate (K3Fe(CN)6 / K4Fe(CN)6·3H2O) was used as an electrode pair to configure 0.4MFe(CN)6 3- / Fe(CN)6 4- Electrolyte solution (i.e., Fe(CN)6 3- The concentration of ions is 0.4M, Fe(CN)6 4-The concentration of ions is also 0.4M); take Bi 0.4 Sb 1.6 The Te3 block was broken, ground in an agate mortar for 15 minutes, and then subjected to a planetary mill at 300 rpm for 3 hours to obtain micron-sized Bi 0.4 Sb 1.6 Te3 particles, particle size distribution Figure 1 As shown; take 1mL 0.4M Fe(CN)6 3- / Fe(CN)6 4- Electrolyte solution with 2.4 g micron-sized Bi 0.4 Sb 1.6 Te3 particles were placed in a brown bottle and magnetically stirred for 30 min to obtain an electrolyte slurry of a mixture of an electrode and a microelectrode. The mixture was filled in a silicone tube with an inner diameter of 5 mm, and the gold-plated copper column electrode and the silicone tube were locked with a wire to obtain a thermoelectric-electrochemical cell with a high Seebeck coefficient, which converts a pure redox electrode electrolyte solution (only 0.4 MFe(CN)6 3- / Fe(CN)6 4- )’s Seebeck coefficient increased from 1.4mV / K to 4.11mV / K, and the output power was 0.1W / m 2 Increased to 0.9W / m 2 ,like Figure 3 shown.
[0050] Example 2
[0051] Potassium ferrocyanide / potassium ferrocyanide trihydrate (K3Fe(CN)6 / K4Fe(CN)6·3H2O) was used as an electrode pair to configure 0.4MFe(CN)6 3- / Fe(CN)6 4- Electrolyte solution; take Bi 0.4 Sb 1.6 The Te3 block was broken, ground in an agate mortar for 15 minutes, and then subjected to a planetary mill at 300 rpm for 3 hours to obtain micron-sized Bi 0.4 Sb 1.6 Te3 particles, particle size distribution Figure 1 As shown; take 1mL0.4M Fe(CN)6 3- / Fe(CN)6 4- Electrolyte solution with 3.2 g micron-sized Bi 0.4 Sb 1.6Te3 particles were placed in an agate ball mill and ball-milled at 150 rpm for 10 min to obtain an electrolyte slurry of a mixture of an electrode and microelectrodes; the mixture was filled in a silicone tube with an inner diameter of 5 mm, and the gold-plated copper column electrode and the silicone tube were encapsulated with silicone rubber to obtain a thermoelectric-electrochemical cell with a high Seebeck coefficient, which increased the Seebeck coefficient of the pure redox electrode electrolyte solution from 1.4 mV / K to 3.47 mV / K, with an output power of 0.1 W / m 2 Increased to 0.64W / m 2 ,like Figure 3 shown.
[0052] Example 3
[0053] Potassium ferrocyanide / potassium ferrocyanide trihydrate (K3Fe(CN)6 / K4Fe(CN)6·3H2O) was used as an electrode pair to configure 0.4MFe(CN)6 3- / Fe(CN)6 4- Electrolyte solution: 1 mL 0.4 M Fe(CN)6 3- / Fe(CN)6 4- The electrolyte solution and 0.5g of commercial nano-indium oxide (purchased from Aladdin, <100nm) were placed in a brown bottle and magnetically stirred for 30min to obtain an electrolyte slurry mixed with an electrode and a microelectrode; the electrolyte slurry was filled in a silicone tube with an inner diameter of 5mm, and the gold-plated copper column electrode and the silicone tube were locked with a wire to obtain a thermoelectric-electrochemical cell with a high Seebeck coefficient, which increased the Seebeck coefficient of the pure redox electrode electrolyte solution from 1.4mV / K to 2.15mV / K, and the output power was 0.1W / m 2 Increased to 0.26W / m 2 ,like Figure 3 shown.
[0054] Example 4
[0055] Potassium ferrocyanide / potassium ferrocyanide trihydrate (K3Fe(CN)6 / K4Fe(CN)6·3H2O) was used as an electrode pair to configure 0.4MFe(CN)6 3- / Fe(CN)6 4- Electrolyte solution; take Bi 0.4 Sb 1.6 The Te3 block was broken, ground in an agate mortar for 15 minutes, and then subjected to a planetary mill at 300 rpm for 3 hours to obtain micron-sized Bi 0.4 Sb 1.6 Te3 particles, particle size distribution Figure 1 As shown; take 1mL0.4M Fe(CN)6 3 - / Fe(CN)6 4-Electrolyte solution with 2.4 g micron-sized Bi 0.4 Sb 1.6 Te3 particles were placed in a brown bottle and magnetically stirred for 30 minutes to obtain an electrolyte slurry mixed with a redox couple and a microelectrode; a graphite electrode was first encapsulated at one end of a 20mm inner diameter polytetrafluoroethylene frame, and then a cut hydrophilic polyurethane sponge with a diameter of 20mm was filled in, and the electrolyte slurry was slowly dripped in until it was full, and the graphite electrode was encapsulated with bolts. A high Seebeck coefficient thermoelectric-electrochemical cell was obtained, which increased the Seebeck coefficient of the pure redox couple electrolyte solution from 1.4mV / K to 4.11mV / K, and the output power was 0.1W / m 2 Increased to 1.05W / m 2 ,like Figure 3 shown.
[0056] Example 5
[0057] Potassium ferrocyanide / potassium ferrocyanide trihydrate (K3Fe(CN)6 / K4Fe(CN)6·3H2O) was used as an electrode pair to configure 0.4MFe(CN)6 3- / Fe(CN)6 4- Electrolyte solution; take Bi 0.4 Sb 1.6 The Te3 block was broken, ground in an agate mortar for 15 minutes, and then subjected to a planetary mill at 300 rpm for 3 hours to obtain micron-sized Bi 0.4 Sb 1.6 Te3 particles, particle size distribution Figure 1 As shown; take 1mL0.4M Fe(CN)6 3- / Fe(CN)6 4- Electrolyte solution with 2.4 g micron-sized Bi 0.4 Sb 1.6 Te3 particles are placed in a brown bottle and stirred magnetically for 30 minutes to obtain an electrolyte slurry mixed with an electrode pair and a microelectrode; a graphite electrode is first encapsulated at one end of a polytetrafluoroethylene frame containing 16 (4×4) battery cavities with an inner diameter of 20 mm, and then a cut hydrophilic polyurethane sponge with a diameter of 20 mm is filled in, and the electrolyte slurry is slowly dripped in until it is full, and the graphite electrode is encapsulated with bolts and 16 batteries are connected in series with copper wires. A thermoelectric-electrochemical battery pack with a high Seebeck coefficient can be obtained, which obtains an open circuit voltage of 1.83V at a temperature difference of 30°C, which can drive LED lights and electronic watches, such as Figure 4 shown.
[0058] Example 6
[0059] Take potassium iodide / iodine (KI / I2) as the electrode pair to configure 0.5MI - / I3 -Electrolyte solution (I3 - KI3 can be introduced by directly reacting KI and I2 in equal amounts. That is, the raw materials for preparing the electrolyte solution can be KI and I2 in a molar ratio of 2:1. In the obtained electrolyte solution, I - The concentration of ions is 0.5M, I3 - The concentration of ions is also 0.5M); take 1mL 0.5MI - / I3 - The electrolyte solution and 0.45g of commercial nano zinc oxide (purchased from Aladdin, 90±10nm) were placed in a brown bottle and magnetically stirred for 30min to obtain an electrolyte slurry of a mixture of an electrode and a microelectrode; the mixture was filled in a silicone tube with an inner diameter of 5mm, and the gold-plated copper column electrode and the silicone tube were locked with a wire to obtain a thermoelectric-electrochemical cell with a high Seebeck coefficient, which converts a pure redox electrode electrolyte solution (only 0.5MI in the electrolyte) into a - / I3 - The Seebeck coefficient of the redox couple (without the introduction of nano zinc oxide) increased from 0.35mV / K to 1.15mV / K, such as Figure 5 shown.
[0060] Example 7
[0061] Take ferric trifluoromethanesulfonate / ferrous trifluoromethanesulfonate as the electrode pair to prepare 0.1M Fe 3+ / Fe 2+ Electrolyte solution (i.e., Fe 3+ The concentration of ions is 0.1M, Fe 2+ The concentration of ions is also 0.1M); take 1mL 0.1MFe 3+ / Fe 2+ The electrolyte solution and 0.5g of commercial nano-indium oxide were placed in a brown bottle and magnetically stirred for 30min to obtain an electrolyte slurry of a mixture of an electrode and a microelectrode. The mixture was filled in a silicone tube with an inner diameter of 5mm, and the gold-plated copper column electrode and the silicone tube were locked with a wire to obtain a thermoelectric-electrochemical cell with a high Seebeck coefficient, which converts a pure redox electrode electrolyte solution (only 0.1M Fe in the electrolyte) into 3+ / Fe 2+ , without the introduction of nano-indium oxide), the Seebeck coefficient increased from 1.21mV / K to 1.73mV / K, an increase of about 43%. Figure 5 shown.
[0062] Example 8
[0063] Potassium ferrocyanide / potassium ferrocyanide trihydrate (K3Fe(CN)6 / K4Fe(CN)6·3H2O) was used as an electrode pair to configure 0.4MFe(CN)6 3 - / Fe(CN)6 4- Electrolyte solution; take Bi 0.4 Sb 1.6 The Te3 block was broken, ground in an agate mortar for 15 minutes, and then subjected to a planetary mill at 300 rpm for 3 hours to obtain micron-sized Bi 0.4 Sb 1.6 Te3 particles, particle size distribution Figure 1 As shown; take 1mL0.4M Fe(CN)6 3- / Fe(CN)6 4- Electrolyte solution with 1.2 g micron-sized Bi 0.4 Sb 1.6 Te3 particles were placed in an agate ball mill and ball milled at 150 rpm for 10 min to obtain an electrolyte slurry of a mixture of an electrode and microelectrodes; the mixture was filled in a silicone tube with an inner diameter of 5 mm, and the gold-plated copper column electrode and the silicone tube were encapsulated with silicone rubber to obtain a thermoelectric-electrochemical cell with a high Seebeck coefficient, which increased the Seebeck coefficient of the pure redox electrode electrolyte solution from 1.4 mV / K to 1.78 mV / K, with an output power of 0.1 W / m 2 Increased to 0.21W / m 2 .
[0064] Example 9
[0065] Potassium ferrocyanide / potassium ferrocyanide trihydrate (K3Fe(CN)6 / K4Fe(CN)6·3H2O) was used as an electrode pair to configure 0.4MFe(CN)6 3- / Fe(CN)6 4- Electrolyte solution: 1 mL 0.4 M Fe(CN)6 3- / Fe(CN)6 4- The electrolyte solution and 0.3g of commercial nano-indium oxide (purchased from Aladdin, <100nm) were placed in a brown bottle and magnetically stirred for 30min to obtain an electrolyte slurry mixed with an electrode and a microelectrode; the electrolyte slurry was filled in a silicone tube with an inner diameter of 5mm, and the gold-plated copper column electrode and the silicone tube were locked with a wire to obtain a thermoelectric-electrochemical cell with a high Seebeck coefficient, which increased the Seebeck coefficient of the pure redox electrode electrolyte solution from 1.4mV / K to 1.78mV / K, and the output power was 0.1W / m 2 Increased to 0.19W / m 2 .
[0066] Example 10
[0067] Potassium ferrocyanide / potassium ferrocyanide trihydrate (K3Fe(CN)6 / K4Fe(CN)6·3H2O) was used as an electrode pair to configure 0.4MFe(CN)6 3- / Fe(CN)6 4- Electrolyte solution: 1 mL 0.4 M Fe(CN)6 3- / Fe(CN)6 4- The electrolyte solution and 1.5g of commercial nano-indium oxide (purchased from Aladdin, <100nm) were placed in a brown bottle and magnetically stirred for 30 minutes to obtain an electrolyte slurry mixed with an electrode and a microelectrode; the electrolyte slurry was filled in a silicone tube with an inner diameter of 5mm, and the gold-plated copper column electrode and the silicone tube were locked with a wire to obtain a thermoelectric-electrochemical cell with a high Seebeck coefficient, which increased the Seebeck coefficient of the pure redox electrode electrolyte solution from 1.4mV / K to 1.62mV / K, and the output power was 0.1W / m 2 Increased to 0.15W / m 2 .
[0068] The above embodiments are only examples. For example, the concentration of the electrolyte solution can be flexibly adjusted (for example, the concentration of the electrolyte solution can be controlled to be as large as possible within the electrolyte solubility range). The size of the microelectrode in the present invention is micro-nano level, and the smallest can be as small as tens of nanometers (such as 50nm) and the largest can be as large as tens of microns (such as 50μm). In addition, the semi-solid battery electrolyte filling slurry configured based on the present invention can be matched with a variety of battery packaging methods, which can be applicable to the conversion of low-grade thermal energy to electrical energy under various working conditions.
[0069] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A thermoelectric-electrochemical cell based on a redox couple, characterized in that: The electrolyte of the battery is dispersed with redox couples and micro-electrodes, wherein the micro-electrodes are selected from oxide micro-nano particles and semiconductor compound micro-nano particles; Wherein, the oxide material of the oxide micro-nano particles is at least one of TiO2, ZnO, ZrO2, In2O3, ATO, FTO, ITO, AZO, and SnO2; The semiconductor compound of the semiconductor compound micro-nano particles is at least one of a Bi2Te3-based compound, a SnTe-based compound, a MgAgSb-based compound, and an InSb-based compound.
2. The thermoelectric-electrochemical cell based on a redox couple according to claim 1, characterized in that: The redox couple is specifically Fe(CN)6 3- / Fe(CN)6 4- Redox couple, I - / I3 - Redox couple, Fe 2+ / Fe 3+ One of the redox couples.
3. The thermoelectric-electrochemical cell based on a redox couple according to claim 1, characterized in that: The Bi2Te3-based compound is Bi 0.4 Sb 1.6 Te3、Bi2Te 2.7 Se 0.3 At least one of .
4. The thermoelectric-electrochemical cell based on a redox couple according to claim 1, characterized in that: The micro-electrode is the oxide micro-nano particle, and the oxide micro-nano particle is specifically nano oxide particle, and the concentration of the oxide micro-nano particle in the electrolyte is 0.3-1.5 g / mL.
5. The thermoelectric-electrochemical cell based on a redox couple according to claim 1, characterized in that: The micro-electrodes are the semiconductor compound micro-nano particles, which are specifically micron-sized semiconductor compound particles, and the concentration of the semiconductor compound micro-nano particles in the electrolyte is 1.2-3.2 g / mL.
6. The thermoelectric-electrochemical cell based on a redox couple according to claim 1, characterized in that: The semiconductor compound micro-nano particles are specifically semiconductor compound microparticles, which are obtained by grinding or planetary ball milling a smelted semiconductor compound block.
7. Thermoelectric-electrochemical cell based on redox couple according to claim 6, characterized in that: The rotation speed used in the planetary ball milling process is 200-500 rpm, and the processing time is 2-5 hours.
8. The method for preparing a thermoelectric-electrochemical cell based on a redox couple according to any one of claims 1 to 7, characterized in that: The following steps are involved: (S1) dissolving a redox couple in deionized water to prepare an initial electrolyte solution; (S2) mixing the microelectrode with the initial electrolyte solution obtained in step (S1) and dispersing them evenly to obtain a composite electrolyte slurry; (S3) Using the composite electrolyte slurry obtained in the step (S2) as a battery electrolyte, a thermoelectric-electrochemical battery based on a redox couple is constructed.
9. The preparation method according to claim 8, characterized in that: In the step (S3), the battery electrolyte is adsorbed on the sponge, and the two are packaged together inside the battery.
10. The preparation method according to claim 9, characterized in that: The sponge is a melamine sponge or a polyurethane sponge.
11. The preparation method according to claim 8, characterized in that: In the step (S2), the dispersion is specifically carried out by dispersing the microelectrodes in the electrolyte solution through magnetic stirring, ball milling or ultrasonic treatment.
12. The preparation method according to claim 11, characterized in that: Magnetic stirring was performed at a speed of 300-600 rpm for at least 20 min; Ball milling is performed in an agate ball milling jar using agate ball milling beads at a speed of 150-250 rpm for 10-30 min; Ultrasonication is to seal the mixed slurry in a serum bottle and ultrasonicate it for more than 1 hour, and shake it every 15-30 minutes during the treatment process.
Citation Information
Patent Citations
Redox fuel cell
CN101821890A
Aqueous thermochemical battery of high Seebeck coefficient and a device
CN109616678A